Coagulation of the Suspended Organic Colloids Using the Electroflocculation Technique - Moayedi, H.; Kazemian, Sina; Vakili, A.H.; Ghareh, S.; Nazir, R. (TAYLOR & FRANCIS INC, 2014)
Electroflotation is an unconventional separation process owing its name to the bubbles generation method (i.e., electrolysis of the aqueous medium) caused by the hydrogen and hydroxide development. Collecting the colloidal particles in surface water has been a long-term issue all over the world, because of their adverse influence. In the present research, the electroflocculation technique have been use to collect the humus particles throughout the polluted wastewater. The uses of different chemical additives namely, Al2(SO4)3, Al(OH)3, CaCl2, CaO, and Na2SiO3 were also successfully examined and enhanced the electroflocculation technique. Although high negatively surface electrical charge of humus causes difficulties in the conventional flocculation and coagulation technique, it enhances the flocculation process when the electroflocculation techniques have been used. The results of both Jar test and electroflocculation technique are further compared. It can be concluded that the polluted water were fully decontaminated (i.e., all of the suspended colloids through the water were removed) by using the electroflocculation technique. The removal rate after electroflocculation test were 91.8%, 98%, 93.5%, 85.3%, 95.4%, and 94% for neutral, Al2(SO4)3, Al(OH)3, CaCl2, CaO, and Na2SiO3, respectively. While the removal rate after Jar test were 84.8%, 83.79%, 71.44%, 84.83%, 77.09%, and 77.09% for neutral, Al2(SO4)3, Al(OH)3, CaCl2, CaO, and Na2SiO3, respectively. © 2014 Copyright Taylor and Francis Group, LLC.